2019
DOI: 10.3390/biom9120828
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Synergistic Inhibition on α-glucosidase by Phytoalexins in Soybeans

Abstract: To determine the mechanism of action of the effects of phytoalexins in soybeans, we analyzed α-glucosidase inhibition kinetics using Michaelis–Menten plots and Lineweaver–Burk plots. The results showed that the type of inhibition with glyceollin was competitive, that of genistein was noncompetitive, that of daidzein was uncompetitive, and luteolin showed a mixed mode of action. The Ki values were determined using a Dixon plot as glyceollin, 18.99 μM; genistein, 15.42 μM; luteolin, 16.81 μM; and daidzein, 9.99 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 30 publications
3
14
0
Order By: Relevance
“…Thus, the model shows the binding cavity of a rare uncompetitive inhibitor, which is similar to the binding mode of daidzein reported previously. 21 The main residues forming hydrogen bonds involved in the binding model of 3 to α-glucosidase were Val 406, Glu 404, Arg 338, Thr 336 and Asp 335. In detail, three hydrogen bonds were formed between the hydrogen atoms of C2′-OH, C3′-OH, and C4′-OH of 3 and Thr336, Glu404, respectively.…”
Section: Molecular Dockingmentioning
confidence: 99%
“…Thus, the model shows the binding cavity of a rare uncompetitive inhibitor, which is similar to the binding mode of daidzein reported previously. 21 The main residues forming hydrogen bonds involved in the binding model of 3 to α-glucosidase were Val 406, Glu 404, Arg 338, Thr 336 and Asp 335. In detail, three hydrogen bonds were formed between the hydrogen atoms of C2′-OH, C3′-OH, and C4′-OH of 3 and Thr336, Glu404, respectively.…”
Section: Molecular Dockingmentioning
confidence: 99%
“…However, it is also essential to further confirm whether the antioxidant activity of the combination of α-tocopherol plus squalene or other volatile compounds in GIE is synergistic. Moreover, the synergistic action of such compounds from plants had been calculated by the combination index (CI) [40][41][42].…”
Section: Antioxidant Capacity Of Giementioning
confidence: 99%
“…However, the estrogen-like activities of isoflavonoids in extracts are expected to differ from their activities in pure form. Indeed, it has been reported that the ER-dependent transcriptional activity of isoflavones in pure form is different from that in mixture with other components [ 16 ]; and that cell uptake of isoflavone aglycones may be affected by companion isoflavonoids interfering with the hydrolysis of their respective glucosides by membrane glucosidases [ 17 ]. Nonetheless, genistein and its glucosides are likely to predominantly determine the estrogenic-like activities of the extracts, given that the ER-binding affinity and estrogen-agonist activity of genistein are much higher than those of the other isoflavones detected in the eight extracts [ 10 ].…”
Section: Resultsmentioning
confidence: 99%